Proveniência sedimentar da borda nordeste da Bacia Bauru, Minas Gerais, Brasil : insights sobre o arcabouço estratigráfico, análise composicional e geocronologia UPb de zircões detríticos - Gabriella Vago Piffer (2020)
ABSTRACT The Bauru Basin developed in an intracontinental setting during the Cretaceous, in the South American Platform, but there is no consensus on the subsidence mechanisms involved in its origin. Alluvial fans deposits characterize the upper sedimentation of the basin and are restricted to the northern and eastern edges, such as the Marília Formation, which originated in the Maastrichtian. The origin of the Marília Formation is presented here as an important tool to assist in understanding how the final basin filling occurred. This paper aims to elucidate the source characteristics, through compositional data analysis of sediments and U-Pb ages of detrital zircons, and to understand the controlling factors by means of an analysis of the stratigraphic framework. The study area is located on the northeast edge of the Bauru Basin, where the Adamantina and Marília formations occur. The contact between the two units is identified as an unconformity (S1) characterized by the prograding alluvial fan system over deposits of a paleoenvironment dominated by meandering rivers. The top of Adamantina Formation represent a Low-Amalgamation System Tract (LAST) and the Marília Formation deposits are subdivided into a High-Amalgamation System Tract (HAST) at the base, and a Low-Amalgamation System Tract (LAST) at the top, separated by a sub-aerial unconformity (S4). Other minor sub-aerial unconformities (S2 and S3) limit depositional cycles in HAST and the source study is focused on the first one, in the basal deposits of Marília Formation. Paleocurrents indicate the sources to be between northeast and northwest of the basin, while compositional data indicate the signature of recycled orogens, with an increasing tendency of the quartz ratio, and geochronological U-Pb data of detrital zircons reveal ages from Mesoarquean to Carboniferous. The higher age density indicates the origin of the zircons during the Brazilian Orogeny while younger ages show the reworking of the Paraná Basin, that complies with the compositional results. Tectonism is identified as the main allocyclic factor that originated the Marília Formation deposits, however climatic factors such as the increased aridity, also influence the internal depositional cycles of HAST. Tectonic activities are associated with reactivations of former basement structures, which were responsible for causing the reworking of the Paraná Basin. The study suggests the potential contribution of reactivations in the region of Rondonópolis Anteclise, the northwest border of Bauru Basin. The reactivation mechanisms may be related to the efforts arising from the opening of the Atlantic Ocean combined with the Andean compressive efforts.